Non-thermal Food Processing Technologies for Reducing Microbial Loads - Akanni, Sodiq Femi; Oke, Moruf Olanrewaju; Olatunde, Sogo James (The Indonesian Institute of Science and Technology Research, 2024)
This study provides a comprehensive review of non-thermal food processing technologies and their effectiveness in preventing microbial contamination and improving food quality. Non-thermal treatments, including high-pressure processing (HPP), pulsed electric fields (PEF), ultraviolet (UV) irradiation, plasma treatment, and ohmic heating, offer innovative alternatives to traditional thermal methods for microbial control. These technologies leverage mechanisms such as pressure, electrical energy, light, or reactive species to achieve microbial inactivation while preserving sensory attributes and nutritional integrity. Despite their considerable potential, non-thermal treatments face challenges and limitations related to technological complexity, regulatory considerations, cost implications, and efficacy against specific microorganisms or food matrices. Addressing these challenges requires collaboration between industry stakeholders, regulatory agencies, and research institutions to drive innovation, establish regulatory frameworks, and optimize implementation strategies. By overcoming current limitations and harnessing the full potential of non-thermal treatments, the food industry can enhance food safety, quality, and sustainability while meeting consumer demands for safe and minimally processed foods.